2003
DOI: 10.1523/jneurosci.23-06-02239.2003
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Promotes Proliferation of Striatal Neuronal Progenitors by an NMDA Receptor-Mediated Mechanism

Abstract: Increasing evidence suggests that classical neurotransmitters play important roles in the development of the mammalian CNS. We used in vivo and in vitro models to identify a novel role for glutamate in striatal neurogenesis mediated by NMDA receptors. In utero exposure to NMDA receptor antagonists during striatal neurogenesis caused a dramatic reduction in the total number of adult striatal neurons. In contrast, embryos exposed to NMDA receptor antagonists immediately after the main period of neurogenesis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(140 citation statements)
references
References 123 publications
13
127
0
Order By: Relevance
“…ANOVA did not reveal significant differences among the 3 experimental groups in total numbers of NeuNpositive or NeuN-negative cells in any of the regions analyzed. Our estimates of total cell numbers in the caudate putamen and frontal cortex are consistent with estimates by others [29,40,48]. However, we were concerned that the penetration of the NeuN or the secondary antibody into the histological sections during the immunohistochemistry procedure may be uneven or incomplete (i.e.…”
Section: Stereological Estimates Of Total Numbers Of Neun-positive Ansupporting
confidence: 88%
See 1 more Smart Citation
“…ANOVA did not reveal significant differences among the 3 experimental groups in total numbers of NeuNpositive or NeuN-negative cells in any of the regions analyzed. Our estimates of total cell numbers in the caudate putamen and frontal cortex are consistent with estimates by others [29,40,48]. However, we were concerned that the penetration of the NeuN or the secondary antibody into the histological sections during the immunohistochemistry procedure may be uneven or incomplete (i.e.…”
Section: Stereological Estimates Of Total Numbers Of Neun-positive Ansupporting
confidence: 88%
“…An unbiased stereological technique, the optical fractionator [29,30,68], was used to estimate the total number of NeuN-positive and NeuN-negative cells in the caudate-putamen and frontal cortex [29,30]. The equipment consisted of a light microscope (Nikon E2000) connected to a cool CCD camera (Microfire; Optronics, Goleta, CA), motorized X-Y stage (Ludl Electronics Products, Hawthorne, NY), z-axis indicator (MT12 microcator; Heidenhain, Traunreut, Germany), and a computer running Stereo Investigator software (Microbrightfield, Inc., Colchester, VT).…”
Section: Stereologymentioning
confidence: 99%
“…Interestingly, glutamate may have dichotomous effects on neurogenesis, depending on its concentrations. Low concentrations of exogenous glutamate (10 mM) introduced to cell or slice culture led to increased NPC proliferation and neurogenic potentials [19][20][21], whereas high concentrations of exogenous glutamate (300 mM) introduction resulted in impaired DNA synthesis and reduced cellular proliferation [25]. Second, glutamate has a direct neurotoxic effect on mature neurons [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The product of glutaminase-catalyzed reaction is glutamate, a classical and the most abundantly used excitatory neurotransmitter. Glutamate has long been implicated in the maturation of neurons [18][19][20][21]. Specifically, an in vitro study on NPCs has revealed the role of glutamate in neuronal differentiation through the activation of AMPA receptors [20].…”
Section: Introductionmentioning
confidence: 99%
“…Neurospheres derived from the embryonic rat brain express the NR1 and NR2B subunits of the NMDA receptor and show reductions in diameter and number (Mochizuki et al, 2007). Furthermore, the activation of NMDA receptors increases the proliferation of neuronal progenitors in the developing hippocampus (Joo et al, 2007) and striatum (Luk et al, 2003) as well. These findings are consistent with the present results.…”
Section: Discussionmentioning
confidence: 99%